PESTA ADAT SEBAGAI SARANA PEMBELAJARAN NILAI BUDAYA DALAM PENDIDIKAN MASYARAKAT DI DESA ALOR KECIL KECAMATAN ALOR BARAT LAUT KABUPATEN ALOR - Nurlaila B Arsyad; Tabita Plaikari; Halena Muna Bekata; Umiyani Kona, Trivonia Atta, Tabita A Serangkai, Tersia Lengmalu, Petrus Mau Tellu Dony (Adisam Publisher, 2025)
This study aims to examine traditional festivals as a means of learning cultural values in community education in Alor village, Alor Barat Laut sub-district, Alor regency. The research data analysis uses qualitative descriptive analysis. The data used in the study is qualitative data. The data collection techniques used were field observation and interviews. The interviewee was Mr Karim Antoni. The traditional festival also serves as a medium to strengthen social relations between residents and to educate the younger generation about the importance of preserving local traditions and culture. The activities in the traditional festival, such as traditional rituals, traditional dances, and traditional deliberations, are a learning forum that involves all members of the community. Based on the research results, it can be concluded that the traditional festival in Alor Kecil Village is not only part of the tradition, but also functions as a means of cultural education. This traditional festival is effective in instilling cultural values in the community, especially the younger generation, while maintaining the sustainability of local cultural traditions and identity.